Peran Media Sosial dalam Pemerolehan Bahasa Remaja (Studi Kasus di UPTD SMP Negeri 1 Parepare, Sulawesi Selatan) - Juanda Juanda (Universitas Cokroaminoto Palopo, 2023)
Adolescents experience many developments that affect their language acquisition. The goal of this research is exploring the role of social media in language acquisition for 13-year-old youth at Yunior High School Negeri 1 Parepare, South Sulawesi. This study uses a descriptive method, which describes the results of the research in the form of findings regarding the words that adolescents acquire when using social media. The data for this study came from two teenagers, namely JNT (13 years) and NRH (13 years) who were students in class VII.1 who were female. The research data was obtained through three methods, namely, observation, recording online, and interviews. Researchers observed the use of social media among students and provided online questionnaires containing questions about new words obtained from social media every day. To support these data, researchers conducted interviews with the two research subjects. The results of this study indicate that social media plays a positive role in language acquisition for adolescents aged 13 years. Through social media, the two research subjects acquired 53 new words within two weeks. The words obtained can be grouped into seven parts, namely standard words which are technical (scientific) words by 26%, terms in certain fields and English (code mixing) each by 15%, slang (prokem) by 11%, classical Indonesian (which is commonly used in literature) by 8%, standard (popular) words by 6%, and others (Indonesian literary varieties, non-standard technical words, Javanese, Latin, Sanskrit, abbreviations , and poetic language) by 19%. The results of this study are very appropriate for teachers to use digital-based learning media in learning Indonesian, especially material related to vocabulary.